Assessment of the physical internet enabled urban logistics using agent-based simulation. Issue 4 (22nd August 2019) - Zheng, Long; Beem, Pieter; Bae, Ki-Hwan G.
The physical internet (PI) is a new paradigm in logistics to aim for more efficiency and sustainability via the shared use of hubs and transports as well as the consolidation of shipments. This study investigates the potential of an open mobility web, designed on the principles of PI, in an urban area with e-commerce warehouses. Our motivation is to understand benefits gained by incorporating PI into existing logistics networks. To that aim, a multi-agent based simulation model is developed to demonstrate the efficacy of our proposed solution approach in this modelling framework. Four transportation scenarios simulate a range of advancements from the traditional logistics to PI. The computational results using real data indicate that the PI-enabled mobility web outperforms the traditional logistics on most performance measures of time and cost. We conclude with implications for logistics stakeholders, and discuss limitations and extensions of this study.